Al-Ulūhiyatu ‘Inda Mu’taqadi Sapta Darma wa Sumarah (Dirāsah Muqāranah) - Muhammad Nurrosyid Huda Setiawan*; Nadya Amaliyah* (Departement of Comparative Study of Religions, 2021)
As one of the Almighty creatures, humans will certainly never be separated fromthoughts about their God. Divinity is one of the sacred things which mediates howhumans appreciate worship to their Creator. Even though it is well known that God isOne with such worship, it turns out that there are several ethnic groups and cultureswhich collaborate this divine concept with their culture or what is called the Javanesetradition. Of the many Javanese traditions in Indonesia, the Sapta Darma and Sumarahtraditions are examples of how a Javanese culture has its own divine concept. Whichis still an interesting topic and object to study. There are several similarities betweenthe Sapta Darma an Sumarah traditions. As for what is the similarity between thesetwo schools is regarding the concept of prostration which becomes the intermediarybetween the adherents and his creator. Not only in terms of the similarities found,the author also found differences between these two schools, including regardinghow these two schools interpret divinity between perspectives, with the existence ofthe Pancasila of God for example, or with other things. Not only that, regarding thenature of God and God’s relationship with humans, in fact, these two schools haveunique definitions. Therefore, this paper aims to expand on this material in detail.Specifically, this paper aims to explore a little how the meaning of divinity accordingto the Javanese tradition in Indonesia. This study employed comparative analysis tocompare the divine concept according to the Sapta Darma and Sumarah schools. Andsupported by a theological approach that is really focused on the concept of divinity